Communicative Language Teaching Approach to Enhance Speaking Skill - García Poveda, Dayana Alexandra (2026)
Speaking skill is regarded as one of the essential skills to be developed during the process of acquiring a new language. The present study aimed to analyze how the Communicative Language Teaching method contributes to the development of Speaking skill in Third-semester students of Pedagogy of National and Foreign Languages degree at Universidad Nacional de Chimborazo in Riobamba. The investigation adopted a quantitative approach, collecting quantified data subject to statistical analysis using a Pre-test and Post-test. The research is applied in nature, and due to its pre-experimental design, both instruments were applied to the same sample size of 25 students. The Cambridge Preliminary English Test (PET) served as the instrument for both the Pre-test and Post-test. The intervention strategy was implemented over four weeks with two hours of instruction per week to ensure the viability of the results. Furthermore, data analysis was performed using the Statistical Package for the Social Sciences (SPSS) software. As a result, the alternative hypothesis was accepted, as the Post-test mean (14.96) exceeded the initial Pre-test mean (12.56). The research findings demonstrated significant improvements in speaking skill, particularly when students were exposed to communicative activities such as role-plays, debates, oral presentations, and dialogues